Case Report: Early-Onset Guillain–Barre Syndrome Mimicking Stroke - Sun, Jing; Gao, Yu; Chi, Lumei; Cao, Qingyang; Ning, Zhijie; Nan, Guangxian (Frontiers in Neurology, 2021)
Introduction: Guillain–Barre syndrome (GBS) is an acute immune-mediated inflammatory demyelinating polyneuropathy characterized by symmetrical limb weakness and areflexia. GBS can have different clinical manifestations; hence, the initial symptoms are also varied. Here, we describe a rare case of GBS presenting as hemiparesis and cranial nerve palsy, which mimic brainstem stroke. Case Presentation: A 53-year-old man was admitted to the hospital with a 3-h history of left-arm weakness, glossolalia, and right eyelid droop. After admission, his condition suddenly worsened, with quadriplegia, bilateral peripheral facial palsy, bilateral ophthalmoplegia, and other neurological symptoms. Based on the findings from a neurological examination, MRI, cerebrospinal fluid analysis, and nerve conduction study, a diagnosis of GBS was made. He received intravenous immunoglobulin (0.4 kg/day) for 5 days. After 20 days of systematic therapy, his dysphagia, dyspnea, facial paralysis, ocular movement disorder, and leg weakness recovered almost completely, but his arms were still moderately impaired, with a power of 4/5. Fortunately, the patient recovered well without any sequelae after 2 years of follow-up. Conclusions: In patients with an atypical presentation, the diagnosis of GBS is often delayed. With this case report, we intend to highlight the fact that some symptoms mimicking stroke may be a feature of GBS at onset; close observation and timely diagnosis are crucial for clinicians. Neuroimaging is a valuable diagnostic tool in differentiating stroke from GBS.